THE IMPACT OF AWARENESS AND TRUST ON UPTAKE OF HEALTH INSURANCE AMONG UNIVERSITY STUDENTS. A CASE STUDY OF UGANDA CHRISTIAN UNIVERSITY, MUKONO CAMPUS. - WAI ELIA NELSON (UGANDA CHRISTIAN UNIVERSITY, 2025)
This study examined The Impact of Awareness and Trust among University Students. A Case Study of Uganda Christian University, Mukono Campus. Globally, health insurance is considered as a cornerstone for achieving UHC. However, in Uganda, the coverage of health insurance remains critically low below 5% with university students representing the underinsured group despite of them being literate, technologically aware, and highly exposed to health-related risks. The study specifically examines the role of awareness and trust as behavioural factors for influencing students’ health insurance uptake. The research adopted a cross-sectional descriptive and analytical design. A sample of 60 final year Bachelor of Business Administration students was selected through stratified random sampling. The data was collected using a semi-structured questionnaire and then analysed using SPSS (version 26). The descriptive statistics summarized the demographic characteristics, awareness, trust, and uptake levels of health insurance. For relationships and mediation effects, Pearson correlation, logistic regression, and Hayes’ PROCESS Macro (Model 4) were employed for assessment. The findings revealed that health insurance among university students was very low with only 20% of students enrolled and mostly family schemes therefore indicating a lag in independent venture. It further established that awareness levels were moderate(mean=3.25) but gaps persisted in understanding of claim procedures and entitlements. Trust levels were below average(mean=3.00) with mean of 2.98 which reflected scepticism about insurers’ transparency, fairness, and service quality. Both awareness (r=0.579, p< 0.01) and trust (r=0.646, p< 0.01) significantly correlated with willingness to pay, though trust showed a stronger effect. Mediation analysis established that trust partially mediated the relationship between awareness and uptake with logistic regression confirming that trust and awareness explain jointly 64.2% of variations in health insurance uptake. This suggested that awareness alone does not guarantee enrolment unless coupled with confidence in insurers’ credibility and service delivery. The study concluded that low health insurance uptake among university students is more of a function of the behavioural barriers than mere financial constraints. Trust emerged as a stronger predictor of health insurance uptake than awareness, suggesting the need to complement awareness campaigns with deliberate trust building initiatives. This study therefore, contributes to the behavioural dimension of health insurance uptake literature in Sub- Saharan Africa by highlighting trust as a critical mediator between awareness and actual enrolment
UNDERGRADUATE RESEARCH